The Railway Children - E Nesbit (London Usborne Publishing Ltd, 2011)
This is an evocative picture book based on the classic E. Nesbit tale. When their father disappears, Bobbie, Peter and Phyllis move out of London and experience new exciting adventures in the countryside. But will their father ever return? It features illustrations taken from the popular "Young Reading" series.
Jr.Kg
Keywords: Risk and Challenges; PY-UOI-Who We Are